Porto Alegre Line predicts lenticulostriate arteries encasement and extent of resection in insular gliomas. A preliminary study - Isolan, Gustavo Rassier; Bark, Samir Ale; Monteiro, Jander Moreira; Mattei, Tobias A.; Yağmurlu, Kaan; Gonçalves, Rafaela Fernandes; Malafaia, Osvaldo; Roesler, Rafael; Filho, Jurandir Marcondes Ribas (Frontiers in Surgery, 2025)
ObjectIn insular glioma surgery, lenticulostriate arteries (LSTa) tumoral encasement increases neurological deficits risk despite intensive efforts to preserve the internal capsule's integrity. In this study, we focus on the LSTa relationships with the medial aspect of the insular tumors. We propose a new non-invasive method for LSTa involvement prediction in preoperative MRI (Porto Alegre Line). We compare it with direct intraoperative encased LSTa visualization.MethodsA retrospective review of our database of 52 patients of insular glioma was performed. In cases with no tumor located medial to Porto Alegre line, our medial resection limit, mainly for the tumor part located next to the limen insula, was the inferior fronto-occipital fasciculus (IFOF), identified through altered speech patterns during electric subcortical stimulation. In cases with no assumed LSTa involvement, the parameter used to stop resection was the confirmation of the corticospinal tract with 10-mA stimulus. The resection limit of tumors placed medially to the Porto Alegre line was intraoperative direct LSTa visualization.ResultsThe LSTa involvement was the most critical medial limiting factor in more aggressive tumor resection and an excellent overall survival (P = 0.022). In cases in which there were direct intraoperative LSTa encasement visualization, Porto Alegre Line was employed as an MRI preoperative landmark for prediction of LSTa involvement in those patients with Sensitivity, Specificity, Positive Predictive Values of 1, 0.975 and 0.923, respectively.ConclusionWe have found that LSTa encasement is a limiting factor to reach a satisfactory extent of resection and that Porto Alegre Line can predict it.